2012
DOI: 10.3892/ijo.2012.1530
|View full text |Cite
|
Sign up to set email alerts
|

Periostin activates integrin α5β1 through a PI3K/AKT-dependent pathway in invasion of cholangiocarcinoma

Abstract: Periostin (PN) is mainly produced from stromal fibroblasts in cholangiocarcinoma (CCA) and shows strong impact in cancer promotion. This work aimed to investigate the mechanism that PN uses to drive CCA invasion. It was found that ITGα5β1 and α6β4 showed high expression in non-tumorigenic biliary epithelial cells and in almost all CCA cell lines. PN had preferential binding to CCA cells via ITGα5β1 and blocking this receptor by either neutralizing antibody or siITGα5 could attenuate PN-induced invasion. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
82
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 46 publications
(61 reference statements)
9
82
0
Order By: Relevance
“…29 The PI3K/Akt pathway plays a fundamental role in the development of gastric cancer, 30 and accumulating evidences have indicated that periostin can promote cancer cell growth and inhibit apoptosis by activating the PI3K/Akt pathway in human cancers, such as colon cancer, cholangiocarcinoma, prostate cancer, and non-small-cell lung cancer (NSCLC). 8,[31][32][33] Conversely, periostin plays a tumor-suppressor role in bladder cancer by repressing its activity. 32 Moreover, periostin has also been revealed to exhibit a biphasic effect on Akt activity in pancreatic cancer cells with an increase of Akt activity at the high concentration but a decrease at the low concentration.…”
Section: Discussionmentioning
confidence: 96%
“…29 The PI3K/Akt pathway plays a fundamental role in the development of gastric cancer, 30 and accumulating evidences have indicated that periostin can promote cancer cell growth and inhibit apoptosis by activating the PI3K/Akt pathway in human cancers, such as colon cancer, cholangiocarcinoma, prostate cancer, and non-small-cell lung cancer (NSCLC). 8,[31][32][33] Conversely, periostin plays a tumor-suppressor role in bladder cancer by repressing its activity. 32 Moreover, periostin has also been revealed to exhibit a biphasic effect on Akt activity in pancreatic cancer cells with an increase of Akt activity at the high concentration but a decrease at the low concentration.…”
Section: Discussionmentioning
confidence: 96%
“…Intriguingly, it has been shown that reduced Atf3, Egr1, Itgb1, and Akip1 levels leads to Akt inactivation (20 -23), whereas up-regulation of Postn and Rfxp1 (24,25) or down-regulation of Egln3 promotes Akt activation (26) (Fig. 4G).…”
Section: Generation Of Mir-223 Transgenic Mousementioning
confidence: 91%
“…However, liver weight and TG content were significantly reduced in Postn-heterozygous mice and MPHs (Supplemental Figure 14), which suggests that fatty acids might also be involved in regulation of periostin expression in obesity-associated hepatosteatosis. It has been reported that periostin exerts its biological functions through several signaling pathways in the development of human cancers, including PI3K/AKT and Wnt/β-catenin (12,34,35). However, AKT phosphorylation was not altered in livers of mice overexpressing periostin.…”
Section: Disruption Of Postn Improves Hepatosteatosis In Obese Micementioning
confidence: 93%